1991
DOI: 10.1039/c39910000824
|View full text |Cite
|
Sign up to set email alerts
|

Application of indium ate complexes to synthetic chemistry. Selective conjugate addition to enones and coupling with allylic halides

Abstract: Tetraorganoindium ate complexes, prepared by the addition of organolithium reagents to trialkylindium, reacted with a,@-unsaturated ketones in a 1,4-addition fashion; allylic indates derived from allylic indium sesqui halides coupled with allylic halides regio-and stereo-specifically to give high yields of head-to-tail 1,5-dienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…The 1,4-conjugate addition reaction of organoindium compounds has previously been studied by Araki et al, who reported that triorganoindium compounds are unreactive toward enones but that some tetraalkylindates add in a 1,4-fashion in moderate yields . In our experiments the reactivity of triorganoindium compounds with enones was also low, giving <10% yields of the tertiary alcohol product of the 1,2-addition (Scheme ); the main component of the reaction mixture was unreacted enone.…”
Section: Resultssupporting
confidence: 56%
“…The 1,4-conjugate addition reaction of organoindium compounds has previously been studied by Araki et al, who reported that triorganoindium compounds are unreactive toward enones but that some tetraalkylindates add in a 1,4-fashion in moderate yields . In our experiments the reactivity of triorganoindium compounds with enones was also low, giving <10% yields of the tertiary alcohol product of the 1,2-addition (Scheme ); the main component of the reaction mixture was unreacted enone.…”
Section: Resultssupporting
confidence: 56%
“…During the course of this study, we considered the possibility of extending the metal-catalyzed crosscoupling reaction by using indate complexes. While tetramethylindate was prepared and structurally elucidated as the first indate complex, its application to organic synthesis was not reported except for selective conjugate addition to α,β-enones and substitution with allylic halides . In addition, trivalent organoindiums are among the indium reagents that were most generally investigated in many organic reactions .…”
mentioning
confidence: 99%
“…Reaction of 4-phenyl-3-buten-2-one, which is a unique example of an α,β-unsaturated ketone, with allylindium reagents produces a regioselective 1,2-addition product . However, there are few reports on the Michael addition reaction to α,β-unsaturated ketones using allylindium reagents . Recently, it was reported that indium-mediated allylation to 1,1-dicyano-2-arylethenes gave Michael addition products in aqueous media in good yields 6a.…”
mentioning
confidence: 99%
“…However, there are few reports on the Michael addition reaction to α,β-unsaturated ketones using allylindium reagents . Recently, it was reported that indium-mediated allylation to 1,1-dicyano-2-arylethenes gave Michael addition products in aqueous media in good yields 6a. Tetraorganoindium ate complexes reacted with α,β-unsatursated ketones in a 1,4-addition fashion 6b.…”
mentioning
confidence: 99%
See 1 more Smart Citation